Yours emotionally: How emotional intelligence infuses public service motivation and affects the job outcomes of public personnel. (28th July 2017) - Levitats, Zehavit; Vigoda‐Gadot, Eran
Abstract : We investigate the role of emotions in the public sector and their relation with work outcomes typical of public arenas. We focus on the emotional intelligence of public healthcare staff and its potential impact on public service motivation, job satisfaction, affective commitment and the quality of service to citizens. Using data from 200 nurses in a large Israeli public hospital, we examine a mixed model of direct and indirect relationships. The findings support direct positive relationships between emotional intelligence, public service motivation and job outcomes, and several indirect relationships: (1) the mediating effect of public service motivation in the relationship between emotional intelligence and affective commitment, and (2) the moderating role of emotional intelligence in the relationship between public service motivation and service quality. The impact of public service motivation on self‐reported service quality is stronger for public employees with more emotional intelligence.